Importers, Exporters and Multinationals: Exploring the Hierarchy of International Linkages - Joakim Gullstrand; Karin Olofsdotter; Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2014)
The purpose of this paper is to empirically explore two dimensions of the firm hierarchy of international market-specific linkages using data for Swedish manufacturing firms over the 1997 to 2007 period. First, we investigate the productivity ordering with respect to importing, exporting and investing abroad. Second, we investigate the productivity ordering with respect to linkage complexity (i.e. the number of linkages at firm level). Our findings support a general productivity hierarchy from importing to exporting and then investing abroad as well as from low- to high-linkage complexity. However, an industry-by-industry examination shows that the hierarchical structure is only generally upheld for linkage complexity while the ordering of the three linkages does not exhibit the same regularity across industries. In extending the analysis, we find these irregularities to be upheld by industry characteristics. Lastly, we go beyond the productivity ordering and explore firm characteristics correlated with the linkage complexity.
Keywords: F14; F21; F23; 330; manufacturing firms; productivity ordering; market linkages